Efektivitas Lama Perendaman Serbuk Kulit Jeruk Manis (Citrus sinensis) Terhadap Bilangan Peroksida Pada Minyak Jelantah - Nastiti Kartikorini; Baterun Kunsah; Diah Ariana (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2021)
Used cooking oil is the remaining cooking oil from the frying process. The use of cooking oil repeatedly at high temperatures and for a long time causes the peroxide number to increase. High peroxide levels can present a health hazard. Phenolic and flavonoid content contained in sweet orange peel is an antioxidant that acts as an antidote to free radicals so that it can slow down the oxidation of used cooking oil. The purpose of this study was to determine the effectiveness of the long soaking time of the sweet orange peel powder (Citrus sinensis) on the peroxide number in used cooking oil. This type of research is experimental with the number of sample repetitions for each treatment, namely 25 samples. The formulation of the problem of this research is whether there is an effect of the effectiveness of the long soaking time of the sweet orange peel powder (Citrus sinensis) on the peroxide number in used cooking oil. From the results of the examination, the average levels of peroxide numbers in used cooking oil that had been soaked were 1 day 22.7949 mEq, 2 days 19.5965 mEq, 3 days 13.5975 mEq and 4 days 9.5984 mEq. Statistical analysis using ANOVA showed the effect of the effect of soaking duration of sweet orange peel powder (Citrus sinensis) on the peroxide number in used cooking oil p (sig) = 0,000 which is less than 0.05.  Keywords:  Sweet Orange, Peroxide Number, Used Cooking Oil.